The Influence of Movement Tempo on Acute Neuromuscular, Hormonal, and Mechanical Responses to Resistance Exercise-A Mini Review - Wilk, Michal; Tufano, James J; Zajac, Adam (Journal of strength and conditioning research, 2020)
Wilk, M, Tufano, JJ, and Zajac, A. The influence of movement tempo on acute neuromuscular, hormonal, and mechanical responses to resistance exercise-a mini review. J Strength Cond Res 34(8): 2369-2383, 2020-Resistance training studies mainly analyze variables such as the type and order of exercise, intensity, number of sets, number of repetitions, and duration and frequency of rest periods. However, one variable that is often overlooked in resistance training research, as well as in practice, is premeditated movement tempo, which can influence a myriad of mechanical and physiological factors associated with training and adaptation. Specifically, this article provides an overview of the available scientific literature and describes how slower tempos negatively affect the 1-repetition maximum, the possible load to be used, and the number of repetitions performed with a given load, while also increasing the total time under tension, which can mediate acute cardiovascular and hormonal responses. As a result, coaches should consider testing maximal strength and the maximal number of repetitions that can be performed with each movement tempo that is to be used during training. Otherwise, programming resistance training using various movement tempos is more of a trial-and-error approach, rather than being evidence or practice based. Furthermore, practical applications are provided to show how movement tempo can be adjusted for a variety of case study-type scenarios.
Keywords: odporový trénink; svalová síla; fyziologická adaptace; Movement; Muscle Strength; Resistance Training; kosterní svaly; pohyb; Humans; mužské pohlaví; Male; lidé; Muscle, Skeletal; Adaptation, Physiological